2021
DOI: 10.20414/betajtm.v14i1.399
|View full text |Cite
|
Sign up to set email alerts
|

Students’ reflective thinking based on their levels of emotional intelligence in mathematical problem-solving

Abstract: [English]: This qualitative research aims to analyze secondary students’ reflective thinking in solving mathematical problems based on their emotional intelligence (EI). It involved four secondary school students selected from twenty-nine students who were given the EI questionnaire. The research instrument was a test and an interview guideline. Data analysis was referred to as Polya's four problem-solving stages integrated with the indicators of reflective thinking. The findings reveal that students with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The indicators of reflective thinking in this study, as shown in Table 1. (Source: Utomo et al, 2021;Suharna, 2018) One of the topics in 8 th -grade Mathematics is the Pythagorean theorem. The Pythagorean theorem is related to right triangles and involves squares and square roots.…”
Section: A Introductionmentioning
confidence: 99%
“…The indicators of reflective thinking in this study, as shown in Table 1. (Source: Utomo et al, 2021;Suharna, 2018) One of the topics in 8 th -grade Mathematics is the Pythagorean theorem. The Pythagorean theorem is related to right triangles and involves squares and square roots.…”
Section: A Introductionmentioning
confidence: 99%